True grit - Portis, Charles (Overlook Press, 2010)
In 1870s Arkansas, fourteen-year-old Mattie Ross persuades U.S. Marshal "Rooster" Cogburn to ride into Indian Territory and help her capture the gang of outlaws who murdered her father.